Analisis Cyber-Bullying sebagai Penyalahagunaan Kebebasan Berbicara di Sosial Media - Thionuartha, Kevin; Pernando, Yonky (Fakultas Komputer - Universitas Universal, 2024)
Cyberbullying is a form of protection of freedom of speech that is increasingly prevalent on social media, especially among teenagers. Internal factors such as personality and online habits, as well as external factors such as the social environment and technological developments, are the main causes of this phenomenon. Although social media provides a space for expression, this freedom is often misused, which causes serious psychological impacts for victims. Existing regulations, including the ITE Law, are still not effective enough in handling these cases, so a more comprehensive approach is needed through education, better legal regulations, and awareness of digital ethics to create a safe and responsible online space.